Applied genomics in the improvement of crops grown in Africa - Crouch, J.H.; Ortíz, R. (2004)
Crop biotechnology seems to be in its infancy in Africa, some national researchers are well trained in this area but lack of funding from their national governments does not allow them take advantage of their knowledge and professional skills. Among the agro-biotechnology tools, tissue culture ranks first in the micro-propagated and tree crops. DNA marker-aided breeding for a range of traits (particularly to overcome diseases and pests or low input environments) should become the second most important application of agro-biotechnology in the mid-term. Molecular markers are being used worldwide to tag specific chromosome segments bearing the desired gene(s) to be transferred (or incorporated) into breeding lines (or populations). In this way, indirect selection with co-dominant molecular markers tightly linked to the gene(s) controlling the characteristic(s) of interest improves response to selection, because heritability for co-dominant markers equals to 1. Molecular markers are therefore descriptors that offer reproducible results for characterizing genotypes. Similarly, applied plant genomics also improves the understanding of crop gene pools, which are being enlarged by including transgenes and “native” gene pools. Furthermore, finding new genes adds value to traditional agricultural products. There are many on-going applications of DNA markers in research-for-development and crop improvement for crops grown by African farmers. Marker-assisted selection and –aided introgression are being employed by private and public plant breeders mostly to locate and select genes for controlling important quality and disease or pest resistant traits.